Yardstick competition and public sector innovation - Rincke, Johannes (International Tax and Public Finance, 2009)
The paper addresses the incentives of the public sector to implement new technologies in public service provision. The focus is on the role of local governments under decentralization. Exploiting variation in the level of innovation in a large sample of US school districts, the impact of yardstick competition on the choice of public sector technologies is identified. It is shown that the impact of other districts’ innovation activity on a district’s innovation score is much stronger in communities where incumbents face a high risk of being elected out of office. This finding suggests that under decentralization, yardstick competition is an important force shaping the decisions of local governments to adopt new technologies.
WiSo-Import:2015-03-26:1711
Keywords: public sector innovation; yardstick competition; school districts; public schools